Studi Kasus: Penerapan Teori Self-Care Orem Pada Pasien Post Operasi Katup Mitral - Sucipto Dwitanta (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2023)
Background: Recovery of heart function is an important condition in the process of healing and rehabilitation of patients after valve surgery to return to normal function. After surgery, patients are often immobile due to possible postoperative complications and activity restrictions, so that the patient's physical capacity is at risk of decreasing. Purpose: The aim of this study was to find out the application of Orem's self-care theory to patients after mitral valve surgery. Method: The design in this study uses the case study method. This study focuses on nursing care which emphasizes the use of Orem's self-care theory in practice. The subject in this study was one postoperative mitral valve patient who was treated in the postoperative unit with an implementation time of seven days. Results: In the results of applying Orem's self-care theory, five main nursing diagnoses were found. Most of the nursing problems are rooted in problems with decreased cardiac output due to post-surgical complications, but the complications are gradually improving. The application of Orem's self-care theory provides a systematic pattern of thinking in determining diagnoses and nursing interventions that must be carried out by nurses. Conclusion: The application of Orem's self-care model appears to have an effect on the nursing process, specifically in postoperative mitral valve cases in identifying problems in fulfilling self-care. The application of this model can provide benefits in encouraging patients to carry out activities that are in accordance with the patient's abilities and tolerance.